Proceedings of the 4th International Conference on Research of Educational Administration and Management (ICREAM 2020) 2021
DOI: 10.2991/assehr.k.210212.087
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Implementation of Life Skill Education Management in Students With Disability Between Public Special School and Private Special Schools

Abstract: The implementation of life skills management carried out by schools for students with disabilities has a difference between one school and another, in this article we will analyze the comparison of the implementation of life skill management for students with disabilities in State Special Schools and private Special Schools. The study was carried out at State Special Schools and private Special Schools in Sukabumi District with 10 respondents for each school consisting of the principal, the vice principal of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Consequently, there is a significant disparity between individuals' skill sets and the demands of modern living in this century. Permana et al (2021) assert that the academic curricula supplied to pupils suffer from a noticeable lack of life skills, so it is imperative to enhance and refine this curriculum. A survey study conducted by Ningsih et al (2023) confirmed the lack of life skills among students with learning disabilities in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, there is a significant disparity between individuals' skill sets and the demands of modern living in this century. Permana et al (2021) assert that the academic curricula supplied to pupils suffer from a noticeable lack of life skills, so it is imperative to enhance and refine this curriculum. A survey study conducted by Ningsih et al (2023) confirmed the lack of life skills among students with learning disabilities in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…Life skills refer to the ability to effectively adjust to diverse individuals and meet the demands and obstacles of life, which can differ, depending on the surrounding society and environment (Permana et al, 2021). These skills are commonly seen as fundamental abilities that individuals should develop and internalize to enhance their personal growth and well-being, and they are essential tools that enhance cognitive abilities in personal, professional, and social contexts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation